PENDIDIKAN KESEHATAN KEPADA SISWA TENTANG JAJANAN DAN MAKANAN SEHAT DI SDN KEBONSARI TUBAN - Lilia faridatul fauziah; Tri Yunita Fitria Damayanti; nikita welandha prastiwi; Muhammad zainul ma'arif (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2021)
Street food has become an inseparable part of people's lives, both in urban and rural areas. Children from any group generally like snacks. "Snack culture is part of the daily life of almost all age groups and social classes, including school-age children and adolescents. The nutritional content of snack foods varies, depending on the type, namely as we know main meals, snacks, and drinks. The method of implementing the activity and the solution to this problem is to educate on the management of pregnant women with high risks. This activity was carried out on Tuesday, May 20, 2019 at 09.00-10.00 at SDN Kebonsari Tuban using the lecture and question and answer method using leaflet media and was attended by 20 participants. Healthy snacks are nutritious snacks and do not contain harmful substances. At SDN Kebonsari there are still many students who consume unhealthy snacks but after the Health Education was carried out, students began to understand healthy snacks and could choose which snacks to buy and consume.